Kindergarten management system - Liaw, Hui Kim (2014)
Nowadays, the management system plays important roles in every field such as hospital, school, library and kindergarten. All daily activities can run smoothly with using a systematic management system. Kindergarten Management System is an online system that will contribute to improvements in the management of kindergarten. This system is designed for Aik Kuan Kindergarten to help administrator and teachers in the management of kindergarten. Although the kindergarten is using government online system to manage students and employees data, but the kindergarten still lack of management in student attendance, fees and notification.Kindergarten Management System consists of five modules including Student Registration, Employee Registration, Student Attendance, Student Fees, and SMS Notification. Administrator can use this system to register information of students and managing employees' profile. Teachers can record the student attendance and download monthly attendance reports. Teachers can also download the receipt of fees payment through this system. Teachers can inform late fees payment and administrator can send announcements to parents through SMS using GSM modem. This system can make easier administrator and teachers to retrieve and manage the data in kindergarten. With using SMS alert, the parents can get information of kindergarten faster and easily. Thus, by using this system can benefit to administrators, teachers and parents.